Traditional Sporting Games as Emotional Communities: The Case of Alcover and Moll’s Catalan–Valencian–Balearic Dictionary - Antoni Costes; Jaume March-Llanes; Verónica Muñoz-Arroyave; Sabrine Damian-Silva; Rafael Luchoro-Parrilla; Cristòfol Salas-Santandreu; Miguel Pic; Pere Lavega-Burgués (Frontiers in Psychology, 2021)
Learning to live together is the central concern of education everywhere in the world (UNESCO). Traditional sporting games (TSGs) provide interpersonal experiences that shape miniature communities charged with emotional meanings. The objective of this study was to analyze the ethnomotor features of TSG (relationship between the internal characteristics of the TSG and sociocultural variables) in three Catalan-speaking Autonomous Communities and to interpret them for constructing emotional communities. The study followed a phenomenological-interpretative paradigm. The identification of TSG was done by a hermeneutic methodological approach by using an exhaustive exploratory documentary research. We studied 503 games collected in the Dictionary Català-Valencià-Balear de Alcover and Moll (1926–1963). Instruments and procedure: A database was built up with information about the internal and external logic of the games. The validity of the information was confirmed by means of a concordance test between the researchers. Data processing was carried out by means of classification trees (inferential level), identifying the predictive variables of the types of TSG. Most of the TSGs were sociomotor games (n = 405/503; 80.5%). The classification tree identified four explanatory variables. Three variables were internal traits (body contact, material, and score), and one variable corresponded to external logic (age). Features of the TSG of the Catalan-speaking Autonomous Communities build original emotional communities. The ethnomotor regularities triggered emotional experiences associated with pleasure for (a) living together (predominance of sociomotor games); (b) domesticating of aggressiveness over opponents (different motor licit aggressiveness); (c) developing sustainability (presence and absence of objects from the surrounding environment); (d) educating the competition (games with and without final score); and (e) interpersonal well-being based on the community (transmission of ludic culture from children to young TSG).